Pengaruh Persepsi Siswa dalam Pembelajaran Socio-Scientific Issuess Terhadap Hasil Belajar Siswa Sekolah Dasar - Cindy Tsalsabillah; Wulandari, Fitria (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
The application of the socio scientific issue-based learning approach has an important role because in the socio scientific issue-based learning approach also involves the use of topics or a scientific problem that requires students to be directly involved in dialog, discussion, and debate. This study aims to describe and determine the significant influence between student perceptions of the application of socio scientific issue-based learning on student learning outcomes. This research uses a quantitative approach with a descriptive survey method. The population in this study were all fifth grade students at SDIT El-Haq with the total population or sample used was 26 students in one class. The instruments used were questionnaires about learning based on socio scientific issues and multiple choice questions on student learning outcomes. Then this data was analyzed using simple linear regression analysis. And the results showed that there was a significant influence between students' perceptions of the application of the socio scientific issue-based learning approach on student learning outcomes at SDIT El-Haq